Upaya Tiongkok untuk Menghidupkan Kembali Jalur Sutra dalam Perspektif Balance of Power - Al Hasyim, M Musa (Indonesia Center for Middle East Studies, 2020)
China has regenerated the ancient Silk Road through the BRI (Belt and Road Initiative) scheme throughout the Middle East. The Chinese presence in the region has as well as the new hegemony, slowly shifting the position of the United States and its allies in the Middle East. The escalation of the conflict between Iran and Saudi Arabia does not make China supporting or denying both of them because China keeps the concept of non-intervention in the BRI scheme. The purpose of this study is to analyze the future of the Silk Road BRI by China in the Middle East by using the Balance of Power perspective, especially the Regional Security Complex overview. By conducting an in-depth literature study, the author finds that China is neither eternal friend nor a constant enemy of any Middle East countries. China relation with the countries of the region depends on the future situation. China can have good relations with Iran, Saudi Arabia, Israel, and Palestine at the same time. However, the relationship can change if the United States and some Middle East countries are making new alignment to obstruct China’s hegemony.